Метод синтеза допусковых отклонений на геометрические параметры микрополосковых устройств - Мищенко, М. В.; Фарафонов, А. Ю.; Коваленко, Д. А.; Сицилицин, Ю. А.; Міщенко, М. В.; Фарафонов, О. Ю; Коваленко, Д. А.; Сіциліцин, Ю. О.; Mishchenko, M. V.; Farafonov, A. Y.; Kovalenko, D. A.; Sitsilitsin, Y. A. (My University, 2013)
RU: В представленной работе разработан метод синтеза допусковых отклонений на геометрические параметры микрополосковых устройств. Метод включает в себя: методику расчета схемы микрополосковых линий, основанную на использовании квазидинамических приближений и квазистатического анализа неоднородностей топологии; синтез допусковых отклонений, использующий интервальные модели; оптимизацию допусковых отклонений путем введения весовых коэффициентов; анализ допусков, обусловленных технологическими ограничениями. Приведен пример использования разработанного метода. UK: В представленій роботі розроблено метод синтезу допускових відхилень на геометричні параметри мікросмужкових пристроїв. Цей метод включає в себе методику розрахунку схеми мікросмужкових ліній, яка основана на використанні квазідинамічних наближень та квазістатичного аналізу неоднорідностей топології; синтезу допускових відхилень, що використовує інтервальні моделі; оптимізацію допускових шляхом введення вагових коефіцієнтів; а також аналіз допусків, обумовлених технологічними обмеженнями. Наведено приклад використання методу, що розроблено. EN: Abstract – in this study, the synthesis method of tolerance deviations on the geometrical parameters of microstrip devices was developed. The synthesis and the research of tolerance limits of the geometric parameters single-link hairpin microstrip low-pass filter was provided. Method of calculation of the filter circuit is based on a quasi-dynamic and quasi-static approximation analysis of topology discontinuities. Interval models are used for the synthesis of tolerances. Optimization of geometric tolerances of the filter parameters is performed with weights coefficients. Main technological stages of microstrip microwave devices manufacturing and their resolutions are presented in this research. Deviations of dielectric substrate parameters are limited by producer. Computations showed that taking into account topology discontinuities allows to increase accuracy of microstrip filter frequency responses calculation and also more accurate estimate deviations of frequency responses from nominal values. Analysis of tolerances which are caused by restriction of technologies showed that applying of computation method of frequency responses of filter taking into account topology inhomogeneity allows to estimate possibility of producing of analyzed device on base enterprise.
Метод синтезу допускових відхилень на геометричні параметри мікросмужкових пристроїв
Synthesis method of tolerance deviations to the geometrical parameter of the microstrip devices
Keywords: допусковые отклонения; топологические неоднородности; квазидинамическое приближение; фильтр; допускові відхилення; топологічні неоднорідності; квазідинамічне наближення; фільтр; tolerance deviations; topology discontinuities; quasi-dynamic approximation; filter